EVALUATION OF THE PHARMACY SUPPORT SYSTEM IN THE DETECTION OF DRUG-RELATED PROBLEMS - Andayani, Tri Murti; Rahmawati, Fita; Rochman, Rifky (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The efficiency and speed of a system in identifying DRPs can support and optimize the performance of pharmacists. The objective of this research was to determine the time of analysis and the number of DRPs incidences identified by pharmacists with and without Pharmacy Support Systems (PSS). Methods: The present research was observational with cross-sectional design. The data collection was done prospectively in outpatients at hospital during January 2016. Observations were conducted to the difference between the analysis and the number of DRPs incidence identified by the pharmacists with and without the assistance of PSS. The research population was outpatient at a number of hospitals in Yogyakarta. The tools used in this research were PSS which were a clinical information system that can identify potential DRPs and included three main parts, namely the patients' profile, drug information, and analysis of DRPs. The identification result of DRPs was consisted of six DRPs categories, i.e. without treatment indication, treatment without indication, ineffective drug, too low dose, too high dose, and undesirable drug reactions. Results: Pharmacists without PSS require faster time to analyze the prescription of outpatients. The time majority spent by pharmacists with PSS in reviewing the patients' prescription lies in the length of time the patients enter the therapy-related data obtained manually by patients until the warning being displayed, and making clinical decision related to the DRPs. The statistical test result using Goodness of fit test and Fisher between categories of DRPs incidences detected by pharmacists with and without the assistance of PPS indicates significant differences (P <0.05). Pharmacists with PSS can detect DRPs that are not detected by the pharmacist without PSS. DRPs mostly identified by pharmacists with the assistance of PSS are drug interactions and improper doses. Improper doses primarily identified in geriatric and pediatric patients' prescription. Conclusion: Pharmacists with PSS software can detect DRPs that are not detected by pharmacists only. But pharmacists using the software PSS requires a longer time in the identification of DRPs compared to pharmacists without using PSS. Â 